Evaluation of Rodhradi Gana(Sushrutokta) in Yoni Roga w.s.r. to PCOS (Poly Cystic Ovarian Syndrome) - Meena, Anita; Kaushal, Kamini; Gurjar, Hemwati (International Research Journal of Ayurveda & Yoga, 2022)
Polycystic ovarian syndrome (PCOS) is a common endocrinopathy in women of reproductive age group and an incompletely understood enigmatic disorder of heterogenous nature. It starts appearing at 15 to 25 years of age and it may take years for its clinical presentation to appear. The incidence of polycystic ovarian syndrome is 4% to 22% of women overall and 50% of women seen at infertility clinics. Objective: - Therefore, the objective of this study was to evaluate and efficacy of Ayurvedic treatment (Rodhradi gana ghana and mixture of varun-kanchnar ghana) for PCOS patients. Material & Method: Total of 48 patients were screened at Rajvaidhya Prem shankar sharma govt. Ayurved chikitsalaya, Ambamata, Udaipur. 40 patients satisfied inclusion criteria, and signed informed consent and detailed medical history was recorded. Group-A (20 patient) Rodhradi gana ghana (3gm, 2TDS) for 90 days and Group- B (20 patient) Varun- Kanchnar ghana (3gm, 2TDS) for 90 days were prescribed to the patients. Result: The study was completed by total 40 female patients. There was a 76.74% result of group- A and 49.02% result of group-B, which is statically highly significant.